Adsorption of landfill leachates onto activated carbon: Equilibrium and kinetics - Rivas, F. (2005)
The adsorption of stabilized leachates generated in a municipal landfill onto three commercial activated carbons has been investigated. Norit 0.8, Chemviron AQ40 and Picacarb 1240 have been used as adsorbents. Equilibrium experiments have been conducted to obtain the experimental isotherm profiles. Isotherms have been plotted based on the adsorption of general parameters, for instance chemical oxygen demand, total carbon, absorption at 410 nm and absorption at 254 nm. Different literature models and error functions have been used to adequately fit the experimental data. As a rule of thumb, three-parameter models do adjust experimental results better than two-parameter models. Norit 0.8 shows better adsorption characteristics than the rest of activated carbons, both in terms of contaminant level reduction of per unit mass of absorbent and in terms of the process kinetics.